Vitamin C regulates Schwann cell myelination by promoting DNA demethylation of pro‐myelinating genes. Issue 6 (14th April 2020) - Huff, Tyler C.; Sant, David W.; Camarena, Vladimir; Van Booven, Derek; Andrade, Nadja S.; Mustafi, Sushmita; Monje, Paula V.; Wang, Gaofeng
Abstract: Ascorbic acid (vitamin C) is critical for Schwann cells to myelinate peripheral nerve axons during development and remyelination after injury. However, its exact mechanism remains elusive. Vitamin C is a dietary nutrient that was recently discovered to promote active DNA demethylation. Schwann cell myelination is characterized by global DNA demethylation in vivo and may therefore be regulated by vitamin C. We found that vitamin C induces a massive transcriptomic shift ( n  = 3, 848 genes) in primary cultured Schwann cells while simultaneously producing a global increase in genomic 5‐hydroxymethylcytosine (5hmC), a DNA demethylation intermediate which regulates transcription. Vitamin C up‐regulates 10 pro‐myelinating genes which exhibit elevated 5hmC content in both the promoter and gene body regions of these loci following treatment. Using a mouse model of human vitamin C metabolism, we found that maternal dietary vitamin C deficiency causes peripheral nerve hypomyelination throughout early development in resulting offspring. Additionally, dietary vitamin C intake regulates the expression of myelin‐related proteins such as periaxin (PRX) and myelin basic protein (MBP) during development and remyelination after injury in mice. Taken together, these results suggest that vitamin C cooperatively promotes myelination through 1) increased DNA demethylation and transcription of pro‐myelinating genes, and 2) its known role in stabilizing collagen helices to form the basal lamina that is necessary for myelination. Abstract : Studies have shown that vitamin C promotes Schwann cell myelination via collagen stabilization. However, recent work has found that vitamin C promotes DNA demethylation in vitro and in vivo which regulates transcription. We propose that vitamin C promotes Schwann cell myelination of peripheral nerves by promoting the expression of pro‐myelination genes via DNA demethylation. Vitamin C induces a massive transcriptomic shift in primary cultured Schwann cells while simultaneously producing a global increase in genomic 5‐hydroxymethylcytosine (5hmC), a DNA demethylation intermediate. Vitamin C upregulates 10 pro‐myelinating genes which exhibit elevated 5hmC content in both the promoter and gene body regions of these loci. In modeled mice, dietary vitamin C intake regulates the expression of myelin‐related proteins such as periaxin (PRX) and myelin basic protein (MBP) during development and remyelination after injury.